2019
DOI: 10.1016/j.addbeh.2019.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational social mobility, smoking and smokeless tobacco (snus) use among adolescents during 2008–2017

Abstract: Youth smoking and snus use are strongly associated with the educational track. • The risk for tobacco use is elevated in downward-mobile and stable low adolescents. • Absolute differences in smoking decreased while relative differences increased. • Absolute and relative differences in snus use increased among boys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Finland aims to be tobacco and nicotine free by 2030 [28]. Our results, alongside findings from the earlier investigations showing widening educational differences in tobacco use [1,29], suggest that supporting the less educated is pivotal if this objective is to be reached. Enhanced smoking cessation support should also be targeted at highly addicted smokers, as well as at those with at least moderate symptoms of depression.…”
Section: Discussionsupporting
confidence: 66%
“…Finland aims to be tobacco and nicotine free by 2030 [28]. Our results, alongside findings from the earlier investigations showing widening educational differences in tobacco use [1,29], suggest that supporting the less educated is pivotal if this objective is to be reached. Enhanced smoking cessation support should also be targeted at highly addicted smokers, as well as at those with at least moderate symptoms of depression.…”
Section: Discussionsupporting
confidence: 66%
“…In fact, there has internationally been an increasing trend in youth use of e-cigarettes, snus, and waterpipe in recent years (18)(19)(20)(21). In e.g., USA and Norway, the use of some ATPs has even exceeded the use of conventional cigarettes (22)(23)(24). However, the research on socioeconomic differences in the use of ATPs is somewhat inconsistent and limited, with some research indicating a social gradient in the uptake of ATPs among students from different socioeconomic groups (18,25), while other studies found no socioeconomic differences in the use of ATPs (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Snus is a smokeless tobacco product traditionally used in Scandinavia, most notably in Sweden and Norway, 1 , 2 but also increasingly common in Finland, especially among young adults. 3 Sales of snus is also steadily increasing in the United States, 4 and Swedish Match, the largest snus manufacturer in Sweden, has successfully obtained approval from the U.S. Food and Drug Administration (FDA) to market eight snus products as Modified Risk Tobacco Products on the U.S. market. 4 , 5 Swedish Match has also sought access to the European market, where sale of snus is currently banned, 6 and shown interests in Asian and African markets.…”
Section: Introductionmentioning
confidence: 99%